Examining the predictors of co-worker attitude towards support for breastfeeding at work in clothing factories in Cape Town - Petersen, Rushda (School of Management Studies, 2021)
Return to work is a recurring reason for premature weaning of breastfeeding infants among low-income South African individuals. Yet, breastfeeding research has largely been examined from the health perspective, leaving a gap in the literature regarding research on breastfeeding as a workplace issue. Workplace support is needed to allow the combination of breastfeeding and work to become feasible for women returning to work. Informal support, particularly co-worker support, may be particularly important since formal workplace support are underutilised in low-income settings. This study seeks to provide insight into the factors which contribute to co-worker support for breastfeeding at work in a low-income factory setting, in Cape Town, South Africa. This study examined the relationships between coworkers' attitude towards support for breastfeeding at work and three possible predictors, (1) their perceptions of family supportive supervisor behaviours (FSSB) in the factory, (2) their personal breastfeeding experience and (3) their perceptions of fairness for breastfeeding at work. Furthermore, parental status was examined as a moderator on the relationship between co-workers' perceptions of fairness for breastfeeding at work and their attitude towards support for breastfeeding at work. Blue-collar workers in Cape Town clothing factories responded to the self-report questionnaire (N = 259). The study results revealed that FSSB, personal breastfeeding experience in the community (but not as a mother or in the factory), and perceptions of fairness for breastfeeding at work predicted positive attitude towards support for breastfeeding at work. Parental status did not moderate the relationship between perception of fairness for breastfeeding at work and co-worker attitude towards support for breastfeeding at work. Implications for practice and research are presented.